Assessment of the effects of medium composition on growth, lipid accumulation and lipid profile of Chlorella vulgaris as a biodiesel feedstock - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
Microalgae serve as a potential feedstock for renewable energy-biodiesel production due to their lipid content. Nowadays, it is possible to maximize the lipid content of microalgal cells via biochemical engineering methods. The aim of the presented study is to observe the effects of six different medium compositions on the growth, lipid content and lipid profile of Chlorella vulgaris. © 2015 IEEE.
Keywords: Biodiesel; Chlorella vulgaris; Lipid; Microalgae